Pulmonary toxicity induced by the use of bleomycin in patients with germ cell testicular tumors - Nikolai A. Ognerubov; Tatyana S. Antipova; Sergey A. Ognerubov (Consilium Medicum, 2022)
Introduction. Pulmonary toxicity induced by bleomycin is a dangerous complication of polychemotherapy in patients with germ cell tumors. It occurs with a frequency of up to 46%, and in 14% of cases it is fatal.